Forever Connected: The Lifelong Biological Consequences of Fetomaternal and Maternofetal Microchimerism. (17th December 2020) - Bianchi, Diana W; Khosrotehrani, Kiarash; Way, Sing Sing; MacKenzie, Tippi C; Bajema, Ingeborg; O'Donoghue, Keelin
Abstract: Background: Originally studied as a mechanism to understand eclampsia-related deaths during pregnancy, fetal cells in maternal blood have more recently garnered attention as a noninvasive source of fetal material for prenatal testing. In the 21st century, however, intact fetal cells have been largely supplanted by circulating cell-free placental DNA for aneuploidy screening. Instead, interest has pivoted to the ways in which fetal cells influence maternal biology. In parallel, an increasing appreciation of the consequences of maternal cells in the developing fetus has occurred. Content: In this review, we highlight the potential clinical applications and functional consequences of the bidirectional trafficking of intact cells between a pregnant woman and her fetus. Fetal cells play a potential role in the pathogenesis of maternal disease and tissue repair. Maternal cells play an essential role in educating the fetal immune system and as a factor in transplant acceptance. Naturally occurring maternal microchimerism is also being explored as a source of hematopoietic stem cells for transplant in fetal hematopoietic disorders. Summary: Future investigations in humans need to include complete pregnancy histories to understand maternal health and transplant success or failure. Animal models are useful to understand the mechanisms underlying fetal wound healing and/or repair associated with maternal injury and inflammation. The lifelong consequences of the exchange of cells between a mother and her child are profound and have many applications in development, health, and disease. This intricate exchange of genetically foreign cells creates a permanent connection that contributes to the survival of both individuals.